hMRP8-ATTAC Mice: A New Model for Conditional and Reversible Neutrophil Ablation - Duits, Danique E. M.; Salvagno, Camilla; Raeven, Elisabeth A. M.; Vrijland, Kim; Stip, Marjolein C.; Hau, Cheei-Sing; Kaldenbach, Daphne; de Visser, Karin E. (Cells (Basel, Switzerland), 2022)
Neutrophils are not only crucial immune cells for the neutralization of pathogens during infections, but they are also key players in tissue repair and cancer. Several methods are available to investigate the in vivo role of neutrophils in these conditions, including the depletion of neutrophils with neutralizing antibodies against Ly6G, or the blockade of neutrophil recruitment with CXCR2 inhibitors. A limited number of transgenic mouse models were generated that rely on the disruption of genes important for neutrophil development or on the injection of diphtheria toxin to induce neutrophil ablation. However, these methods have various limitations, including a lack of neutrophil specificity, a lack of long-term efficacy, or a lack of the ability to conditionally deplete neutrophils. Therefore, we generated a transgenic mouse model for the inducible and reversible ablation of neutrophils using the ATTAC (Apoptosis Through Targeted Activation of Caspase 8) approach. With the ATTAC strategy, which relies on the expression of the caspase 8-FKBP fusion protein, apoptosis is induced upon administration of a chemical dimerizer (FK506 analogue) that facilitates the dimerization and activation of caspase 8. In order to achieve specific neutrophil depletion, we cloned the ATTAC construct under the human migration inhibitory factor-related protein 8 (hMRP8) promotor. The newly generated hMRP8-ATTAC mice expressed high levels of the transgene in neutrophils, and, as a consequence, dimerizer injection induced an efficient reduction of neutrophil levels in all the organs analyzed under homeostatic conditions. In situations with extensive pressure on the bone marrow to mobilize neutrophils, for instance in the context of cancer, effective neutrophil depletion in this model requires further optimization. In conclusion, we here describe the generation and characterization of a new transgenic model for conditional neutrophil ablation and highlight the need to improve the ATTAC strategy for the depletion of large numbers of rapidly generated short-lived cells, such as neutrophils.